Biodiversity and abundance of fish in estuarine waters of Sesayap and Sembakung, North Kalimantan, Indonesia - ASBAR LAGA; M. GANDRI HARYONO; RATNO ACHYANI; STEPHANIE BIJA; GAZALI SALIM; MUJIYANTO MUJIYANTO; TAUFIQ AHMAD ROMDONI; SITTI HARTINAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Laga A, Haryono MG, Achyani R, Bija S, Salim G, Mujiyanto, Romdoni TA, Hartinah S. 2025. Biodiversity and abundance of fish in estuarine waters of Sesayap and Sembakung, North Kalimantan, Indonesia. Biodiversitas 26: 5574-5594. The estuary of Sesayap and Sembakung Waters in North Kalimantan, Indonesia are areas which are semi-enclosed where river currents meet with tidal’s. The extreme fluctuations are covered by the availability of food because they get nutrient supplies from the sea and land, so this area get variety of fish in abundance. This study aims to determine the biodiversity and abundance of of fish in the estuarine waters of Sesayap and Sembakung. The research uses a quantitative descriptive method and it was conducted for 4 months from August 2021 to November 2021. The fish caught were obtained from fishermen using various fishing gear, including sero nets, gillnets, mini trawls, and tugu nets. The fish were sorted by species, weighed collectively, and the total length and weight of each individual were measured. Species identification was performed using three intact specimens, following guidelines from the fish identification book. The results of the study of fish species identification using different fishing gears, obtained as many as 28 species found in the tugu fishing gear dominated by white shrimp species with a percentage of 76.78%; as many as 15 species in the gill net dominated by the selangat (Anodontostoma chacunda) fish species at 47.85%; as many as 21 species in the tiger trawl dominated by the nomei (Harpodon nehereus) fish species at 56.93%, and as many as 30 species in the sero fishing gear dominated by the Penaeus sp. species at 69.13%. The highest abundance was white shrimp at 19.19% found in the tugu fishing gear, respectively. This explains that each fishing tool has characteristics that result in different variations in the catch. The ecological implications of these areas as important nursery grounds, migration routes, and feeding grounds require fishing regulations and the selective use of fishing gear to sustainably increase fisheries productivity.